A Study on Performance Analysis of Top Pharma Companies in India - Poddar, Natika; Machado, Alina (SFIMAR Research Review, 2019)
â€˜The ratio analysis technique is the process of identifying the financial strength and weaknesses of a firm by properly establishing the relationship between the items of profit and loss account and balance sheet. This report is an analysis of the financial operations and performance of the companies for the period of five years that is from 2015 to 2019. This report will provide an assessment and analysis of the profitability, liquidity and solvency position and financial performance of the pharma companies. In the analysis, financial ratios were used to gain a critical review of the specific areas of assessment of a company’s performance. The ratios were able to provide a clear view of the overall performance of the companies.